3n-5=-(6+5n)

Simple and best practice solution for 3n-5=-(6+5n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3n-5=-(6+5n) equation:


Simplifying
3n + -5 = -1(6 + 5n)

Reorder the terms:
-5 + 3n = -1(6 + 5n)
-5 + 3n = (6 * -1 + 5n * -1)
-5 + 3n = (-6 + -5n)

Solving
-5 + 3n = -6 + -5n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '5n' to each side of the equation.
-5 + 3n + 5n = -6 + -5n + 5n

Combine like terms: 3n + 5n = 8n
-5 + 8n = -6 + -5n + 5n

Combine like terms: -5n + 5n = 0
-5 + 8n = -6 + 0
-5 + 8n = -6

Add '5' to each side of the equation.
-5 + 5 + 8n = -6 + 5

Combine like terms: -5 + 5 = 0
0 + 8n = -6 + 5
8n = -6 + 5

Combine like terms: -6 + 5 = -1
8n = -1

Divide each side by '8'.
n = -0.125

Simplifying
n = -0.125

See similar equations:

| (4y+8)+(3y-9)+90=180 | | 2(x+1)-x(x+1)=0 | | b-1819=2300 | | 3(d+6)=12(d+3) | | -1.3+0.4= | | 12x+20=3x+209 | | 4x+10=2(3x-11) | | 7x+21=7 | | 6z+6=2(4z-16) | | 2x^2+9x-1= | | 12-9x=74-23x | | -5x+2=2 | | 24x+(-2)=2x+3 | | (2x+1)3-(x+4)5=5-(5x+1) | | g=3+h | | 75x-5x=8x+32 | | 667=29j | | 6+4=10 | | 4z+9=45 | | f=2g | | f=29 | | 30t+42m=18600 | | 28g=-364 | | 4z+9=180 | | 27g=-364 | | x+(x+4)+3x=64 | | a+38=469 | | -(x-4)=2+6 | | y=0.6(5)+5.32 | | y=0.6(3)+5.32 | | x-2*3=12 | | z/22=25 |

Equations solver categories